Genetic Variability for Seed and Seedling Traits in the Advance Breeding Lines of Indian Mustard [Brassica juncea (L.) Czern & Coss] - S.S. MEENA; RAJBIR YADAV; V.V. SINGH (Seed Research, 2026)
Forty five genotypes including six well adapted cultivars and thirty nine advance breeding lines of Indian mustard were evaluated to assess genetic variability for seed and seedling traits. The material showed considerable variability for majority of traits as indicated by genotypic coefficient of variation. High genetic variability was found for seed yield, root length, fresh seedling weight, vigour index, seedling dry weight, shoot length and 1000-seed weight. Broad sense heritability and genetic advance were also found high for root-shoot ratio, fresh seedling weight, root and shoot length, 1000-seed weight and vigour index. Correlation studies revealed positive and significant association of above traits with seed yield. It can therefore be concluded from present study that there exist sufficient scope for yield improvement through selection of 1000-seed weight, root length, root-shoot ratio, fresh seedling weight and vigour index in the segregating material generated by using selected advance lines.